Sequence Analysis of APOA5 Among the Kuwaiti Population Identifies Association of rs2072560, rs2266788, and rs662799 With TG and VLDL Levels - Jasim, Anfal A.; Al-Bustan, Suzanne A.; Al-Kandari, Wafa; Al-Serri, Ahmad; AlAskar, Huda (Frontiers in Genetics, 2018)
Common variants of Apolipoprotein A5 (APOA5) gene have been associated with lipid levels yet very few studies have reported full sequence data in differentfrom various ethnic groups. The purpose of this study was to re-sequenceanalyse the full APOA5 gene sequence to identify variants in 100 healthy Kuwaitis of Arab ethnicities and assess their association with variation in lipid levels in a cohort of 733 samples. Sanger method was used in the direct sequencing of the full 3.7Kb APOA5 and multiple sequence alignment was used to identify variants. The complete APOA5 sequence in Kuwaiti Arabs has been deposited in GenBank ( KJ401315). A total of twenty reported single nucleotide polymorphisms (SNPs) were identified. Two novel SNPs were also identified: a synonymous 2197G>A polymorphism at genomic position 116661525 and a 3’ UTR 3222 C>T polymorphism at genomic position 16660500 based on human genome assembly GRCh37/hg:19. Analysis of genotype and allele frequency revealed nine variants as common with a minor allele frequency (MAF) above 5%. Five SNPs along with the two novel SNPs were selected for validation in a the cohort. Association of those SNPs with lipid levels was tested and minor alleles of three SNPs (rs2072560 , rs2266788 and rs662799) were found significantly associated with TG and VLDL levels. Linkage analysis was also examined and revealed five major haplotype groups that did not have effect on TG levels. This is the first study to report the full APOA5 sequence and SNPs in an Arab ethnic group. Analysis of the variants identified and comparison to other populations suggests a distinctive genetic component in Arabs. The positive association observed for rs2072560 and rs2266788 with TG and VLDL levels confirms their role in lipid metabolism.